Zmanim: A Historical Quarterly (JSTOR)
Zmanim: A Historical Quarterly was founded in 1979 at the School of History in Tel Aviv University. The aim has been to publish articles in Hebrew, on the history of all periods and geographical regions, of the highest academic standards yet in a form accessible not only to specialists but also to a lay readership.
Keywords: Jewish Studies